PENGARUH KUALITAS PRODUK, HARGA DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK PT. MUSTIKA RATUBUANA INTERNASIONAL Tbk. - Aries Tantya Finis; Handoyo Djoko W (Jurnal Ilmu Administrasi Bisnis, 2016)
The decision to purchase some products for beauty that made by women in generally is a reasonable thing to do. Similarly, purchasing decisions of products PT . Mustika Ratubuana International Tbk , which is done by the student Fisip Diponegoro University . Thus , this study will focus on the results that show about the product purchasing decisions PT . Mustika Ratubuana International Tbk that taken by the respondentThe purpose of this study was to determine the presence or absence of the influence of product quality, price and brand image on product purchasing decisions PT . Mustika Ratubuana International Tbk . The case study at the student of Fisip University Diponegoro . The type of this research is explanatory research . Mechanical sampling using non probability sampling which accidental sampling method and purposive sampling . The number of samples taken by 100 respondents . in this research used SPSS version 21.0.Based on the results of the descriptive analysis of 49% indicates that the variable quality of the products included in the category quite well . 44 % indicates that the variable price included in the category of price , 48 % showing that the brand image variables included in both categories. Based on the calculation of the correlation coefficient and the coefficient of determination shows that the purchasing decision can be explained by 82.7 % by the variable quality of product , price and brand image while the rest of 17,3 explained by other factors . Based on the calculation of F test shows that there is influence between product quality , price and brand image to the purchasing decision .The Suggestions in this research is to improve product quality in both the packaging and the benefits of the product . Moreover in terms of price , the price of conformity with quality products must also be upgraded and improved.